Uji Aktivitas Antipiretik Ekstrak Etanol Daun Durian (Durio Zibethinus L.) Pada Tikus Putih Jantan (Rattus Norvegicus) Galur Wistar - Riza Syafira; D Elysa Putri Mambang; Gabena Indrayani Dalimunthe; Haris Munandar Nasution (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Durian leaves have secondary metabolites, namely flavonoids. Flavonoids have shown a wide range of bioactivity, one of which is an antipyretic effect which can be used as a febrifuge. This study aims to examine the antipyretic activity of the ethanol extract of durian leaves (Durio zibethinus L.) against male white rats (Rattus norvegicus) induced by DPT-HB-Hib vaccine. This study uses an experimental method. In this study, durian leaf extract was processed by maceration using 96% ethanol, then treated with secondary metabolites of simplicia and its ethanol extract. To pay for the antipyretic activity of durian leaves (Durio zibethinus L.) the test animals used were 25 and divided into 5 groups, namely negative control (CMC 0.5%), positive control (Paracetamol 1%) and the test dose group, namely the administration of leaf extract durian 200 mg/kg, 300 mg/kg and 400 mg/kg. Each rat was induced intramuscularly with the DPT-HB-Hib vaccine. Temperature measurements were carried out rectally with initial temperature measurements at 5 minute intervals 3 times, 1 hour after induction and 30 minutes for 3 hours. The data obtained were analyzed using the One-way ANOVA (Analysis of Variance) test and the Tukey HSD test. Based on the results of the study, it was shown that the results of the phytochemical screening of durian leaves contained flavonoids, saponins, tannins, alkaloids, steroids/triterpenoids. Of the three doses that experienced a decrease in temperature that was not significantly different from paracetamol, namely at a control dose of 300 mg/kg, because this decrease in temperature was almost close to paracetamol which was positive.